Reconfigurable Antennas for UWB Cognitive Radio Communication Applications (2017)
In this chapter, reconfigurable antennas are reviewed for ultra-wideband (UWB) cognitive radio communication applications. The defected microstrip structure (DMS) has been reviewed and integrated into the UWB antennas to form the desired filtering antennas which can filter out unexpected narrowband signal interferences. Then, switches are incorporated into the filtering UWB antennas to construct the cognitive radio UWB (CR-UWB) antenna to make the antenna switch between the UWB antenna and band-notched UWB antenna. In these CR-UWB antennas, the DMSs are to give the desired notches while the switches are used for realizing the switchable characteristics. Several reconfigurable antennas and CR-UWB antennas are created and investigated. The results show that the designed CR-UWB antenna can switch between different modes, making it amazing for UWB, band-notched UWB, and multiband communication system applications.